Ứng dụng kết quả nghiên cứu xử lý độ rung tuabin p-6-35/5 - Hoàng, Bá Chư (Bộ Giáo dục và Đào tạo, 2013)
Using the research results of thesis B96 - 28 - TĐ – 02. A group of experts has Successfully treated the Rotor of Turbine P - 6 - 35/5 in Power plant of HaBac Nitrogenous fertilizer and chemical Company . The vibration has been considerably reduced and the machine has been put in to operation safely and efficiently.